Some theorems on generalized thermoelastic diffusion - Kumar R.; Kothari S.; Mukhopadhyay S. (My University, 2025)
The objective of the present work is to establish a convolutional type (Gurtin in Arch. Rat. Mech. Anal. 16:34-50, 1964) variational theorem and a reciprocity theorem for the linear theory of generalized thermoelastic diffusion for homogeneous and isotropic elastic solids. © 2010 Springer-Verlag.